STRUCTURE OF THE INFORMATION COMPONENT OF PROFESSIONAL COMPETENCE OF THE FUTURE TEACHER - Drogaytsev О. І. (Pedagogy of Higher and Secondary Education, 2022)
The article investigates the information components structure of future teachers’ professional efficlency and defines the contents of information efficiency.